eHealth Literacy Among College Students: A Systematic Review With Implications for eHealth Education - Stellefson, Michael; Hanik, Bruce; Chaney, Beth; Chaney, Don; Tennant, Bethany; Chavarria, Enmanuel Antonio (JMIR Publications, 2011)
BackgroundeHealth literacy refers to the ability of individuals to seek, find, understand, and appraise health information from electronic resources and apply such knowledge to addressing or solving a health problem. While the current generation of college students has access to a multitude of health information on the Internet, access alone does not ensure that students are skilled at conducting Internet searches for health information. Ensuring that college students have the knowledge and skills necessary to conduct advanced eHealth searches is an important responsibility particularly for the medical education community. It is unclear if college students, especially those in the medical and health professions, need customized eHealth literacy training for finding, interpreting, and evaluating health- and medical-related information available on the Internet. ObjectiveThe objective of our review was to summarize and critically evaluate the evidence from existing research on eHealth literacy levels among college students between the ages of 17 and 26 years attending various 4-year colleges and universities located around the world. MethodsWe conducted a systematic literature review on numerous scholarly databases using various combinations of relevant search terms and Boolean operators. The records were screened and assessed for inclusion in the review based on preestablished criteria. Findings from each study that met inclusion criteria were synthesized and summarized into emergent themes. ResultsIn the final review we analyzed 6 peer-reviewed articles and 1 doctoral dissertation that satisfied the inclusion criteria. The number of participants in each reviewed study varied widely (from 34 to 5030). The representativeness of the results from smaller studies is questionable. All studies measured knowledge and/or behaviors related to college student ability to locate, use, and evaluate eHealth information. These studies indicated that many college students lack eHealth literacy skills, suggesting that there is significant room for improvement in college students' ability to obtain and evaluate eHealth information. ConclusionAlthough college students are highly connected to, and feel comfortable with, using the Internet to find health information, their eHealth literacy skills are generally sub par. College students, especially in the health and medical professions, would be well served to receive more customized college-level instruction that improves general eHealth literacy.